1-deoxy-4-C-hydroxymethyl-3,4-O-isopropylidene-beta-L-ribulofuranose [(2R,3S,4S)-4-(hydroxymethyl)-3,4-O-isopropylidene-2-methyltetrahydrofuran-2,3,4-triol] - Best, D; Jenkinson, S; Booth, K; Fleet, G; Watkin, D (2007)
The stereochemistry of crystalline 1-de-oxy-4-C-hydroxy-methyl-3,4-O- isopropyl-idene-Β-l-ribulofuran-ose, C9H16O5, was unequivocally established by X-ray crystallographic analysis to be the Β-anomer; the absolute configuration was determined by the use of d-ribose as a starting material. © 2007 International Union of Crystallography. All rights reserved.